Orphan black. Season three [videorecording (DVD)] - Maslany, Tatiana; Gavaris, Jordan, 1989-; Hanchard, Kevin (BBC Worldwide Americas, 2015)
Two-time Critics Choice Award-winner Tatiana Maslany returns in the pulse-racing third season of Orphan Black. After the shocking discovery of Project Castor, Sarah and her sister clones are left to battle the top-secret military project producing these lethal male clones. At the same time, Sarah tries to track down her missing twin Helena and an ailing Cosima searches for the key to the synthetic sequences that may keep them all alive. But how far are they willing to go to protect each other and their families, and who can they really trust? Orphan Black is back with more adrenaline-charged action, intrigue and suspense than ever before!